Identifikasi dan Uji Resistensi Bakteri pada Pasien Ulkus Diabetikum di Bangsal Interne RSUP Dr. M. Djamil Padang - Ringga Novelni (Jurnal Penelitian Farmasi Indonesia, 2019)
Diabetic ulcers is one of diabetic mellitus’s chronic complication such as open wound on the skin and can be accompanied by necrotic tissues. High blood glucose levels become a strategic area to the development of bacteria. This study aims to determine the bacterial agent that cause of diabetic ulcer and its resistance to antibiotics. The design of this study was true experiment with diabetic ulcers patients as the subject in the ward interne at RSUP Dr. M. Djamil Padang on period February - April 2019. In this study 10 samples of diabetic ulcer patients were obtained, then bacterial identification and antibiotic resistance test was done against 5 types of antibiotics ciprofloxacin, cefotaxime, meropenem, gentamicin and vankomicin. Consecutively most of bacteria found were Klebsiella pneumonia (40%), Staphylococcus epidermidis (60%). Proteus vulgaris (10%), Proteus mirabilis (10%), Pseudomonas aeruginosa (10%) and Staphylococcus aureus (10%). Ciprofloxacin and Cefotaxime had the highest level of bacterial resistance (40%), while Vancomicin is effective to used in Staphylococcus aureus and Staphylococcus epidermidis.